Beyond Body Mass Index. Is the Body Cell Mass Index (BCMI) a useful prognostic factor to describe nutritional, inflammation and muscle mass status in hospitalized elderly?: Body Cell Mass Index links in elderly. Issue 3 (June 2018) - Rondanelli, Mariangela; Talluri, Jacopo; Peroni, Gabriella; Donelli, Chiara; Guerriero, Fabio; Ferrini, Krizia; Riggi, Emilia; Sauta, Elisabetta; Perna, Simone; Guido, Davide
Summary: Background & aim: The aim of this study was to establish the effectiveness of Body Cell Mass Index (BCMI) as a prognostic index of (mal)nutrition, inflammation and muscle mass status in the elderly. Methods: A cross-sectional observational study has been conducted on 114 elderly patients (80 women and 34 men), with mean age equal to 81.07 ± 6.18 years. We performed a multivariate regression model by Structural Equation Modelling (SEM) framework. We detected the effects over a Mini Nutritional Assessment (MNA) stratification, by performing a multi-group multivariate regression model (via SEM) in two MNA nutritional strata, less and bigger (or equal) than 17. Results: BCMI had a significant effect on albumin (β = +0.062, P = 0.001), adjusting for the other predictors of the model as Body Mass Index (BMI), age, sex, fat mass and cognitive condition. An analogous result is maintained in MNA<17 stratum. BMI has confirmed to be a solid prognostic factor for both free fat mass (FFM) (β = +0.480, P < 0.001) and Skeletal Muscle Index (SMI) (β = +0.265, P < 0.001), assessed by DXA. BCMI also returned suggestive evidences (0.05 < P < 0.10) for both the effect on FFM and on SMI in overall sample. Conclusions: The main result of this study is that the BCMI, compared to BMI, proved to be significantly related to an important marker as albumin in geriatric population. Then, assessing the BCMI could be a valuable, inexpensive, easy to perform tool to investigate the inflammation status of elderly patients.